Program Peningkatan Kecakapan Hidup Berbasis Vocational Skill Untuk Membangun Jawa Wirausaha Mahasiswa Semester Akhir Mahasiswa Universitas Mathla'ul Anwar Banten - susilawati wijaya; Robby Rizky; ayu mira yunita; Zaenal Hakim; Andrianto Heri Wibowo; Aghi Gilar Pratama; Agung Sugiarto; Sri Setyowati; ervi nuraflian susanti; neli nailul wardah; lili sujai (Jurnal Dharmabakti Nagri, 2023)
The community engagement project titled "Program Peningkatan Kecakapan Hidup Berbasis Vocational Skill Untuk Membangun Jiwa Wirausaha Mahasiswa Semester Akhir Mahasiswa Universitas Mathla'ul Anwar Banten" aimed to enhance the life skills and foster an entrepreneurial mindset among final semester students at Universitas Mathla'ul Anwar Banten. The project addressed the need for preparing students to be competent and competitive in the dynamic job market, equipping them with vocational skills and instilling an entrepreneurial spirit to encourage self-employment and job creation. The project utilized a workshop-based approach, targeting 25 final semester students who demonstrated an interest in entrepreneurship. Pre-test and post-test assessments were conducted to evaluate the effectiveness of the workshop in improving participants' knowledge and skills related to life skills and entrepreneurship. The workshop focused on practical skill development through simulations, case studies, and group discussions, alongside providing insights into market understanding, business management, and financial literacy. The results of the project showed a significant improvement in participants' understanding of vocational skills and entrepreneurship, as evidenced by the post-test scores. The workshop succeeded in enhancing the participants' confidence and preparedness to face entrepreneurial challenges. Participants were motivated to explore business opportunities and recognize their potential to contribute to the local economy. Moreover, the workshop facilitated collaborative learning and encouraged participants to share ideas and experiences, fostering a supportive environment for entrepreneurial development. The project emphasized creative thinking and problem-solving, equipping participants with essential skills needed for entrepreneurial ventures. In conclusion, the community engagement project "Program Peningkatan Kecakapan Hidup Berbasis Vocational Skill Untuk Membangun Jiwa Wirausaha Mahasiswa Semester Akhir Mahasiswa Universitas Mathla'ul Anwar Banten" successfully achieved its objectives in improving life skills and cultivating an entrepreneurial mindset among final semester students. The project highlights the significance of vocational skill development and entrepreneurial spirit in preparing graduates for the job market and encouraging self-employment. The workshop's positive impact emphasizes the need for continuous efforts to support the development of competitive and innovative human resources, contributing to the advancement of both individuals and the community.